2013
DOI: 10.1128/cvi.00312-13
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Recombinant Proteins Consisting of Plasmodium vivax Circumsporozoite Protein Allelic Variant-Derived Epitopes Fused with Salmonella enterica Serovar Typhimurium Flagellin

Abstract: A Plasmodium falciparum circumsporozoite protein (CSP)-based recombinant fusion vaccine is the first malaria vaccine to reach phase III clinical trials. Resistance to infection correlated with the production of antibodies to the immunodominant central repeat region of the CSP. In contrast to P. falciparum, vaccine development against the CSP of Plasmodium vivax malaria is far behind. Based on this gap in our knowledge, we generated a recombinant chimeric protein containing the immunodominant central repeat reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
(44 reference statements)
1
24
0
1
Order By: Relevance
“…Serum IgG anti-P. vivax CSP antibodies were detected by enzyme-linked immunosorbent assay (ELISA) as previously described (14,15). The recombinant proteins (100 to 200 ng/well) were used as the solid-phase bound antigen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum IgG anti-P. vivax CSP antibodies were detected by enzyme-linked immunosorbent assay (ELISA) as previously described (14,15). The recombinant proteins (100 to 200 ng/well) were used as the solid-phase bound antigen.…”
Section: Methodsmentioning
confidence: 99%
“…The hybridomas used were obtained from the Malaria Research and Reference Reagent Resource Center (MR4). Polyclonal antibodies against the P. vivax-like epitopes were ob-tained from C57BL/6 mice immunized with the His 6 -FliC-PvCSP-Vivaxlike antigen as described previously (14). MAbs to the His tag were purchased from GE Healthcare Systems.…”
Section: Methodsmentioning
confidence: 99%
“…Flagellin has been successfully used as an adjuvant against a variety of pathogens, including bacteria [9, 14, 36], viruses [10], and protozoans [11]. While effective as an adjuvant in low doses, flagellin also has been shown to lead to an increase in T-cell dependent [14, 37] antibody production [14, 16, 38-40], specifically producing high titers of IgG1 and IgG2a that provide complete protection against a targeted pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, flagellin has been used successfully as an adjuvant against a variety of pathogens, including bacteria [9], viruses [10], and protozoans [11]. Flagellin promotes Th1-type immunity [12], and importantly, it has been shown that previous exposure to flagellin does not impair the ability of the host to induce robust immune responses when it is used as an adjuvant [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Ответ прост: полезные свойства данных белков планируется использовать в рамках принципиально нового и оригинального подхода, который, как предполагается, будет в состоянии нивелировать негативный момент, связанный с низкой селективностью и не высокой амфифильностью дефензинов альфа и тета. Этот подход заключается в создании гибридных белков, на основе fusion-технологии, иначе называемой технологией слитных генно-инженерных конструкций [47][48][49][50][51][52]. При этом, в нашем случае, целью является объединение, в единой "рамке", двух функциональных последовательностей: как собственно дефензина, так и того или иного амфифильного домена (LTABD и/или LTABP) (рис.…”
unclassified